2009
DOI: 10.1123/jpah.6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Insufficiently Physically Active and the Prevalence of Obesity in the United States

Abstract: Background-Numerous public health organizations have adopted national physical activity recommendations. Despite these recommendations, over half of the US population does not meet the minimum recommendation for physical activity, with large variations across individual US states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 13 publications
0
31
0
3
Order By: Relevance
“…44 This might be due to the geographical location from which the sample was recruited, as Colorado residents show higher levels of physical exercise and lower overweight/ obesity rates. 92 In summary, infants with less attention span (boys), as well as greater soothability or more negative food reaction (girls), showed greater increases in standardized weight and were more likely to be overweight/obese at the age of 6 years. Future research needs to replicate these findings and identify underlying behavioral mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…44 This might be due to the geographical location from which the sample was recruited, as Colorado residents show higher levels of physical exercise and lower overweight/ obesity rates. 92 In summary, infants with less attention span (boys), as well as greater soothability or more negative food reaction (girls), showed greater increases in standardized weight and were more likely to be overweight/obese at the age of 6 years. Future research needs to replicate these findings and identify underlying behavioral mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the prevalence of obesity [body mass index (BMI) ≥30.0 kg/m 2 ] in men ranges from 4.0% to 28.3% and in women from 6.2% to 36.5% (Berghöfer et al, 2008). In the United States, the prevalence ranges from 17.8% to 30.9% (Brock et al, 2009). The prevalence among adult women is 16.7% in Selangor, Malaysia (Sidik and Rampal, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As very well known, activity has a significant direct influence to body weight and especially to adequate body mass maintainance, but is important also by itself as a prevention regarding the development of D2 (Defay, 2001;Brock, 2009). In adult population to the group of high active are classified those, who are active 30 minutes or more on at least five days a week, medium active are those, who are active 30 minutes or more 1 to 4 days a week, other are low active.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…It is also very well known that active life style has very good influence also to body mass and in contrary people who are obese are inclined to inactivity, but there is practically no quantitative data available regarding the statistical correlation on the population level among these two variables. The interesting exception represents the paper of Brock (Brock et al, 2009), where the association between insufficiently physically active and the prevalence of obesity is described for the USA in the form of linear regression model. Testing this description in comparison to information from Table 2 and presented activity response showed that it is expected the prevalence of obesity to be slightly lower in EU countries.…”
Section: Fig 7 Prevalence Of Activitymentioning
confidence: 99%
See 1 more Smart Citation